Wearable sensors for assessing disease severity and progression in Progressive Supranuclear Palsy. (April 2023) - Abate, Filomena; Russo, Michela; Ricciardi, Carlo; Tepedino, Maria Francesca; Romano, Maria; Erro, Roberto; Pellecchia, Maria Teresa; Amboni, Marianna; Barone, Paolo; Picillo, Marina
Abstract: Introduction: Progressive supranuclear palsy (PSP) is an atypical parkinsonism characterized by prominent gait and postural impairment. The PSP rating scale (PSPrs) is a clinician-administered tool to evaluate disease severity and progression. More recently, digital technologies have been used to investigate gait parameters. Therefore, object of this study was to implement a protocol using wearable sensors evaluating disease severity and progression in PSP. Methods: Patients were evaluated with the PSPrs as well as with three wearable sensors located on the feet and lumbar area. Spearman coefficient was used to assess the relationship between PSPrs and quantitative measurements. Furthermore, sensor parameters were included in a multiple linear regression model to assess their ability in predicting the PSPrs total score and sub-scores. Finally, differences between baseline and three-month follow-up were calculated for PSPrs and each quantitative variable. The significance level in all analyses was set at ≤ 0.05. Results: Fifty-eight evaluations from thirty-five patients were analyzed. Quantitative measurements showed multiple significant correlations with the PSPrs scores ( r between 0.3 and 0.7; p < 0.05). Linear regression models confirmed the relationships. After three months visit, significant worsening from baseline was observed for cadence, cycle duration and PSPrs item 25, while PSPrs item 10 showed a significant improvement. Conclusion: We propose wearable sensors can provide an objective, sensitive quantitative evaluation and immediate notification of gait changes in PSP. Our protocol can be easily introduced in outpatient and research settings as a complementary tool to clinical measures as well as an informative tool on disease severity and progression in PSP. Highlights: PSP rating scale is the golden standard to evaluate disease severity and progression. Wearable sensors are useful to investigate gait parameters in movement disorders. We showed a correlation between a brief wearable sensor protocol and PSP rating scale. The same protocol was useful to estimate disease severity and progression. In the short term, our protocol is more sensitive to change than PSP rating scale.